A Numerical Approach for the Determination of Mode I Stress Intensity Factors in PMMA Materials - Khelil, F.; Belhouari, M.; Benseddiq, N.; Talha, A. (Engineering, Technology & Applied Science Research, 2014)
An evaluation technique of the KI stress intensity factors (SIF) by a numerical investigation using line strain method is presented in this paper. The main purpose of this research is to re-analyze experimental results of fracture loads from polymethyl-metacrylate (PMMA) specimens (fully finite plates). Stress intensity factor equation calculation is derived from the Williams stress asymptotic expansion. Possible error caused by strain gradients across the gage length is minimized by integrating the equation in the KI calculation. Theoretical and computed values using finite element analysis of stress intensity factors are compared with experimental results. A good agreement is observed between the present approach and experimental values. It is shown that, in the case of a through-plate crack, the stress intensity factor can be calculated with adequate accuracy using the proposed method.